Research Needs in Canadian Industrial Relations: Emerging from the Solitudes - Thompson, Mark (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1992)
To focus this discussion, "industrial relations" is defined as the organizations and processes through which wages, hours and conditions of work are determined for employees who are represented collectively. This definition excludes topics such as labour history, labour economics and labour law, frequently incorporated into industrial relations research, but separate here.Research should address and attempt to explain the significant features of Canadianindustrial relations, as well as provide the bases for predictions of the future. The distinguishing features of the Canadian industrial relations System for these purposes are its fragmentation, extensive legal regulation and pattern of strikes. Research needs should be based on this description of Canadian industrial relations, including the environment of the System, major actors within it, the processes of industrial relations and the results of negotiation.